Analisa Dampak Masuknya Photovoltaic (PV) Dalam Skala Besar Terhadap Performa Sistem Tenaga Listrik - u, ubaidah (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
Abstract Photovoltaic (PV) is a renewable energy generator that produces electrical energy at a certaintime or also called intermittent.. A large number of PV penetrations into the system significantly affects theability of conventional generators to catch up with power due to decreased PV output power or when PVoutput power is not available. This is due to the different characteristics of the lean rate of each type ofgenerator. To overcome the power imbalance in the electric power system with various compositions, it isnecessary to limit the number of PV that is allowed to be installed in the electrical power interconnectionsystem.In this study, the generator and load data were used collectively from the Indonesian National GreatCompany. The power plants used are hydropower plant, steam power plant, geothermal power plant, dieselpower plant, gas engine power plant, and gas power plant. Based on the simulation results, the number of PVthat is allowed to be installed is a maximum of 30 percent of the total generation in a certain generationconfiguration. If the amount of PV exceeds the maximum limit, there will be a power imbalance between thegenerator and the load. If the generator configuration has a large generator capacity and has a high lean rate,PV plants can be connected to the electrical power interconnection of more than 30 percent of the total generation. Keywords Duck curve, photovoltaic, ramping rate, power imbalance.